Embozene™ microspheres induced nonreperfused myocardial infarction in an experimental swine model. Issue 4 (4th May 2012) - Varga‐Szemes, Akos; Kiss, Pal; Brott, Brigitta C.; Wang, Dezhi; Simor, Tamas; Elgavish, Gabriel A.
<x xml:space="preserve">Abstract</x> Objectives To develop a magnetic resonance imaging (MRI) compatible, percutaneous technique for the generation of nonreperfused myocardial infarct (MI). Background Modeling nontreated MI has major importance in the development and preclinical testing of new therapeutic strategies for patients missing the time window suitable for revascularization following MI. Methods In 31 male swine, nonreperfused MI was generated by permanent occlusion of either the LAD or LCX coronary artery using 900 μm Embozene™ microspheres. Animals were monitored for 90 min postocclusion. Surviving animals were followed up for 2 (n = 6), 4 (n = 6), 14 (n = 6), or 56 (n = 6) days. At the end of the planned study session, contrast enhanced MRI, triphenyl‐tetrazolium‐chloride staining, and microscopic histopathology were carried out. Results The mortality rate in this study was 22.6%. Intraoperative arrhythmias occurred in 14 cases: premature ventricular complexes with (5) or without (3) ventricular tachycardia, 2nd degree atrio‐ventricular block (1), and ventricular fibrillation (6). MRI, TTC, and histology confirmed the existence of MI in every case. Macroscopic pathology showed that the microspheres caused a practically total occlusion at the epicardial level of the coronary artery. Multiple infarcts were detected in one case, probably due to unintentional reflux of the microspheres. Microspheres retained in the coronary arteries did not cause any MRI artifact. Conclusions The generation of nonreperfused MI is feasible by percutaneous injection of Embozene into the coronary artery system. The MI model thus obtained is suitable for the purposes of MRI experiments. © 2012 Wiley Periodicals, Inc.